Upaya Pencegahan Penyakit Scabies melalui Edukasi Kesehatan Dengan Metode Team Games Turnamen (TGT) Pada santriwati di Pondok Putri Ridwan Anwarul Halimy Di Desa Sesela Lombok Barat - Baik Heni Rispawati; Dewi Nursukma Purqoti; H.Muhammad Dimyati; Ernawati; Dika Kartika Sari (Bengkulu Institute, 2026)
Scabies is a contagious skin disease, this disease is caused by an infestation of mites namely sarcoptes scabiei humoris variation, the spread of this disease is caused by several factors one of which is poor environmental hygiene and sanitation as well as lack of knowledge. In this community service aims to find out Scabies Prevention Efforts through health education with the Teams games tournament (TGT) method at the Ridwan Anwarul Halimy Islamic boarding school for girls, Sesela village, West Lombok. The method used in this community service is by identifying students who are affected by scabies and then conducting health education about scabies. and after being given counseling about education on the diet of hypertensive clients through supportive education, the community understands how to control themselves so that their hypertension does not recur. Respondents in this community service were 30 female students in class VIII of the Ridwan Anwarul Halimy Islamic Boarding School for Girls. The conclusion of this study is the influence of health education using the (TGT) method on knowledge of scabies prevention at the Ridwan Anwarul Halimy Islamic Boarding School for Girls, Sesela Village, West Lombok. After being given education about scabies prevention, the students understood how to control themselves so as not to get scabies. With this community service activity, it is hoped that health workers and teachers can provide education about scabies prevention to female students to increase knowledge to avoid infectious diseases.